2017
DOI: 10.1111/pde.13172
|View full text |Cite
|
Sign up to set email alerts
|

Score of Toxic Epidermal Necrosis Predicts the Outcomes of Pediatric Epidermal Necrolysis

Abstract: The pediatric-modified tools were not superior to the adult SCORTEN, which accurately predicted outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…An important differential in this group is acute GVHD and determination of causality and management of immunosuppression can be complex. 23,24 Referral for diagnostic testing to a specialist centre with an expertise in drug allergy should be considered in severe cases, 25 especially where avoidance of the causal drug is medically compromising or difficult for the patient. Patch testing and/or T-cell proliferation/cytokine release assays may be useful in children.…”
Section: Management and Long-term Complications 71 How Should Causalmentioning
confidence: 99%
“…An important differential in this group is acute GVHD and determination of causality and management of immunosuppression can be complex. 23,24 Referral for diagnostic testing to a specialist centre with an expertise in drug allergy should be considered in severe cases, 25 especially where avoidance of the causal drug is medically compromising or difficult for the patient. Patch testing and/or T-cell proliferation/cytokine release assays may be useful in children.…”
Section: Management and Long-term Complications 71 How Should Causalmentioning
confidence: 99%
“…The SCORTEN has multiple factors, but three of them—age of at least 40 years, malignancy, and heart rate of at least 120 beats per minute—are less important in children because (1) they are young, (2) they have low rates of malignancy, and (3) their normal heart rate can be over 120 beats per minute if they are younger than four. The SCORTEN, or a pediatric-adapted scoring system, could be used prospectively in studies to predict treatment efficacy by comparing actual with predicted mortality and morbidity 38 . Despite the availability of a validated severity score that helps to predict which patients will have more severe outcomes, the absence of a gold-standard effective therapy for pediatric SJS-TEN means that the decision between supportive care and directed (immunosuppressive) therapy remains challenging.…”
Section: To Treat or Not To Treat That Is The Question… But We Stillmentioning
confidence: 99%
“…A study published in 2017 compared the adult SCORTEN tool with that of two modifications tailored to children for predicting disease outcome and revealed that the predictive power of the new paediatric SCORTENs for SJS/TEN in children was similar to that of the original SCORTEN developed for adults. 11 This patient's SCORTEN 6 was 2, with an associated mortality rate of 12.1%, epidermal detachment > 30%, and HR > 120 bpm.…”
Section: Discussionmentioning
confidence: 79%